Quase humanos, quase máquinas - SANTANA, Fábio de Amorim (2016)
The objective of this research is to analyze the inhuman (LYOTARD, 1990) in the films Metropolis (GER, 1927) Modern Times (USA, 1936) and Cosmopolis (CAN, FRA, POR, ITA, 2012) and their relationship with technology. The three works are linked by the inhuman, so that it comes to the so-called technical and economic development (or progress), as the other inhuman: individual, which is present in our childhood and follows us into adulthood by the recurrence of memory (LYOTARD, 1990). Therefore, time and technology are two key factors in shaping our contemporary humanity. The Metropolis and Modern Times films, by Fritz Lang and Charles Chaplin, respectively, represent the framework of a new humanity in century XX, more and more interested in speed and technological progress. These movies criticize the so-called modernity and its project of comfort, safety and happiness for everyone: only possible by technology. Cosmopolis, by David Cronenberg, updates the discussion. He shows where we are. Metropolis imagine the cities of the future, divided between the privileged and the workers. Modern Times criticizes the industrialization, the Fordism in the 30’s, and requests another future, much more human. While Cosmopolis is the future accomplished: the chaos, the time when the money was so accumulated by the idea of "time is money", that now the capital "sell" (or offers) the Time (itself) in technological products. After all, what a smartphone offers to us? Just time. Time layers. Humans were dragged - since the time of the first two films (the period between the World Wars) - to an inhuman development, where there is no more human alternative, political and economic too, for this time acceleration process. A "managed life" (by the men-corporations, by the financial system) annuls the time, the memory, the body, because it is always trying to program them. One solution would be to go back to the other inhuman (LYOTARD, 1990), to ourselves, to our memories, to recover our non-ready education, executed at a slow speed, that is necessary so that we can digest and live the experiences and emotions. The characters of these three films are looking for the solution for speed. They want their inhumanity (childhood) back. This is the subject of this research: just a reflection on our almost humanity, and on our almost "machinety" in this contemporary society.